Attitudes toward the purchase over the internet on cybernaut students of UNMSM - Pérez, Susan (2011)
The development of informatic technology introduces virtual platforms to purchase over the Internet, which generate benefits for both businesses and consumers, but this type of purchase is not widespread in Peru yet. That is why, taking in account that attitudes involves an assessment of an object and orients behaviour (La Rosa, 1983), we have taken the attitudes towards this form of marketing, as a predictor of Internet users to make or repeat a purchase on-line. Thus, in order to know the level of approximation or rejection (attitudes) toward purchases on-line, which exists in a sample of college students Internet, we designed a range of attitudes towards the purchase through the Internet. It has 16 items, distributed in two dimensions: advantages perceived and risk assessment, taking into account the explanatory model of adoption of innovations developed for kanuka Schiffman (2000), whereby these two dimensions considered in the range of attitudes, are valued by person to make a decision to adopt, postpone or reject an innovation, which in this case is the virtual purchase. The questionnaire was answered by 107 people and the data revealed higher incidence levels of attitude that expresses feelings of approach toward the purchase over the Internet in terms of perceived benefits, but the opposite is for assessment of risk.